Muscle satellite cells are a functionally heterogeneous population in both somite-derived and branchiomeric muscles - Ono, Yusuke (Elsevier, 2010)
Skeletal muscles of body and limb are derived from somites, but most head muscles originate from cranial mesoderm. The resident stem cells of muscle are satellite cells, which have the same embryonic origin as the muscle in which they reside. Here, we analysed satellite cells with a different ontology, comparing those of the extensor digitorum longus (EDL) of the limb with satellite cells from the masseter of the head. Satellite cell-derived myoblasts from MAS and EDL muscles had distinct gene expression profiles and masseter cells usually proliferated more and differentiated later than those from EDL. When transplanted, however, masseter-derived satellite cells regenerated limb muscles as efficiently as those from EDL. Clonal analysis showed that functional properties differed markedly between satellite cells: ranging from clones that proliferated extensively and gave rise to both differentiated and self-renewed progeny, to others that divided minimally before differentiating completely. Generally, masseter-derived clones were larger and took longer to differentiate than those from EDL. This distribution in cell properties was preserved in both EDL-derived and masseter-derived satellite cells from old mice, although clones were generally less proliferative. Satellite cells, therefore, are a functionally heterogeneous population, with many occupants of the niche exhibiting stem cell characteristics in both somite-derived and branchiomeric muscles.